The Role of Love in the Knowledge of God. John of the Cross’ Perspective - Niziński, Rafał Sergiusz (Filozofia Chrześcijańska, 2014)
While metaphysics (Zubiri) and theology (Barth) approach God using notions, which derive from the experience of the world, mystics approach God through union with him (John of the Cross). Whereas in philosophy and theology mind plays the leading role, in mystics’ perspective it is will with its love, which dominates leading to the union with God. Love makes us somehow similar to God (connaturalitas Thomas Aquinas) therefore mind profits from love and its union with God. Mind abandoning notions opens up to the new knowledge scattering from God.